Grain production space reconstruction and land system function tradeoffs in China - Li, Fei; Qin, Zhangxuan; Liu, Xiaolin; Chen, Zehui; Wei, Xiaoli; Zhang, Qiumeng; Lei, Min (Geography and sustainability, 2021)
•China's grain production space was dramatically restructured since 1980.•Trade-offs between land system functions can be identified by Set Pair Analysis.•Ecological services and socio-economic function show inverse synergies during GPSR.•There is a trade-off between grain production and ecological services.•There is a codirectional trade-off between grain production and economic development. Grain production space reconstruction referred to the changes in the quantity, quality and pattern of grain production space caused by functional tradeoffs and conflicts between grain production space, urban-rural development space, and ecological service space. Exploring tradeoffs between land system functions caused by grain production space reconstruction was particularly important for ensuring food security, promoting the construction of ecological civilization, and achieving sustainable development. Therefore, this study identified four relationships of land system functions during the process of grain production space reconstruction (1980–2018) in China by using Set Pair Analysis. Research results showed that the reconstruction of grain production space was achieved mainly through three pathways: Grain for Green, deforestation and reclamation, and urban expansion. Generally, ecological service had spatial negative correlation with grain production, economic development and population carrying capacity (P < 0.01), but grain production, economic development and population carrying capacity were positively correlated with each other (P < 0.01). In the process of grain production space reconstruction, ecological services and economic development, ecological services and population carrying capacity had all shown inverse synergies; there was a tradeoff between grain production and ecological services, a codirectional tradeoff between grain production and economic development, but a strong synergy between economic development and population carrying capacity. However, the functions of land systems only appeared as synergies or tradeoffs, and there were no inverse synergies and codirectional tradeoffs in the separate processes of Grain for Green, deforestation and reclamation, and urban expansion. It can be concluded that the relationships between land system functions were relatively simple in a single process, but it became complex and diverse when multiple processes were integrated for system analysis. [Display omitted]